Factors associated with mechanical ventilation and death of patients due to Sars-CoV2 in a hospital from Mérida, Yucatán - May Euan, JoseFernando; Canul-Aké, Vanessa; Canul-Aké, Claudia Cecilia; Ceballos-Solís, Gabriel (Horizonte Sanitario, 2024)
Objective: Identify the factors associated with the type of artificial respiration and the death of hospitalized patients caused by Sars-Cov2 in a tertiary hospital in Mérida, Yucatán from January to August 2022.Material and methods: Retrospective observational study. Data collection was carried out in May and June 2023 at the Elvia Carrillo Puerto Hospital of the Institute of Security and Social Services of State Workers (ISSSTE) in Mérida, Yucatán. The sample included 100 records from 133 patients who received some type of artificial respiration NIV (non-invasive mechanical ventilation) or IMV (invasive mechanical ventilation) by the inhalation therapy unit, diagnosed with COVID-19 and were hospitalized from January to August 2022. Data were collected through a card and were processed through descriptive statistics, bivariate and multivariate analysis: binary logistic regression (CI= 95%).Results: Of the 100 files included in the study: 40 received NIV and 60 IMV, 56% corresponded to men, 91% were residents in Yucatán, and 85% were born in this same state. Type 2 diabetes and high blood pressure were associated with death due to IMV. Of the total patient records included in the study sample: 37 were discharged home while 63 died in the hospital. The average number of days with mechanical ventilation was higher in those who died and significantly lower in those who were discharged home. In the regression analysis, overweight and older age were predictor variables of death for patients, while having received NIV was a protective factor.Conclusion: Overweight and age were predictive factors for dying from COVID-19 in this study, while the absence of IMV was a protective factor; NIV was a protective factor against death and associated with hospital survival. Keywords: COVID-19; Respiration, Artificial; SARS-CoV-2; Respiratory Distress Syndrome.